Expert Systems in Reference Services, 1st edition - Roysdon, Christine (Routledge, 2020)
This book, first published in 1989, introduces readers to expert systems applications in many areas of library and information science, and presents design and implementation issues encountered by librarians who have developed early systems to address the library reference function. Systems for ready reference, online database access, and enhancement of subject searching in online catalogues are all explored. Theoretical issues related to expert systems are balanced with descriptions of actual systems currently operating or under development. Reference librarians interested in computing and automation, library managers and administrators, as well as teachers and students in library schools, will be fascinated by this account of how expert systems are helping to make the expertise of the reference librarian available in a more consistent and timely fashion and reduce the burden of repetitive, predictable questions for the professional.